1997
DOI: 10.1002/(sici)1520-6343(1997)3:5<381::aid-bspy5>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

A spectroscopic investigation of the formation mechanism of pigment gallstones

Abstract: Further spectroscopic studies of gallstones are reviewed with an emphasis on the formation of black pigment gallstones. This type of gallstone appears mainly in Western countries, with only 3% of the cholelithiasis patients in China having black gallstones. Fourier transform infrared absorption and electron paramagnetic resonance are used as spectroscopic probes of gallstones and their metal bilirubinate components. Nonlinear phenomena in gallstone formation were investigated through the appearance of ring str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…Since the pathogenesis of gallstones is not clearly understood, its analysis-using chemical and spectroscopic techniques have provided some clues [24,25]. Our studies reported herein on children are of special significance as there are no such earlier reports on children in the literature.…”
Section: Discussionmentioning
confidence: 84%
“…Since the pathogenesis of gallstones is not clearly understood, its analysis-using chemical and spectroscopic techniques have provided some clues [24,25]. Our studies reported herein on children are of special significance as there are no such earlier reports on children in the literature.…”
Section: Discussionmentioning
confidence: 84%
“…Concentric rings and fractal patterns are often found in cross-sections of gallstones. But despite some intensive studies, their pattern formation mechanism is not clear. We have previously reported that the metal ion−deoxycholate(DC)-diffusion system is an ideal model to mimic pattern formation of gallstones in vitro, and we studied the system in glass test tubes and agar plates, where the reaction−diffusion process could be considered as being one- and two-dimensional, respectively. , These systems are also widely used in the studies of other periodic and fractal precipitation patterns. However, the pattern formation in these 1- and 2-D systems cannot mimic the real process completely, because the gallstones are actually formed in vivo through a complex and prolonged diffusion and precipitation process in three dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Concentric rings and fractal patterns are often found in crosssections of gallstones. But despite some intensive studies, [1][2][3][4][5] their pattern formation mechanism is not clear. We have previously reported that the metal ion-deoxycholate(DC)diffusion system is an ideal model to mimic pattern formation of gallstones in vitro, and we studied the system in glass test tubes and agar plates, where the reaction-diffusion process could be considered as being one-and two-dimensional, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of the minerals and elemental components that are likely to play a part in GS formation were quantified by SR‐XRF. Several other studies in literature similar to ours have provided some information on the chemical and spectroscopy techniques used by us, thereby providing some clues on the pathogenesis of GS . However, there are no studies from India addressing the role of SR‐μCT and SR‐XRF in mapping the distribution of the mineral and elemental components of GS.…”
Section: Discussionmentioning
confidence: 57%